2022
DOI: 10.21203/rs.3.rs-1260406/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Systematic Review and Meta-analysis of Ivermectin for Treatment of COVID-19: Evidence Beyond the Hype

Abstract: Background: The role of ivermectin in the treatment of COVID-19 is still under debate, yet the drug has been widely used in some parts of the world, as shown by impressive market data and ivermectin-related adverse event reports. The available body of evidence may have changed over the last months, as studies have been retracted and "standards of care" (SOC) used in control groups have changed with rapidly evolving knowledge on COVID-19 rapidly. This review aims to summarize and critically appraise the evidenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…However, a phase 3, double-blind, randomized, placebo-controlled trial indicated that none of the Ivermectin, Fluvoxamine, and Metformin drugs prevented hypoxemia occurrence, hospitalization, and death related to COVID-19 [ 58 ]. In addition, a meta-analysis done on 25 randomized controlled trials in 2022 indicated that Ivermectin doesn't decrease the risk of mortality risk and the risk of mechanical ventilation requirements [ 59 ].…”
Section: Therapeutic Agentsmentioning
confidence: 99%
“…However, a phase 3, double-blind, randomized, placebo-controlled trial indicated that none of the Ivermectin, Fluvoxamine, and Metformin drugs prevented hypoxemia occurrence, hospitalization, and death related to COVID-19 [ 58 ]. In addition, a meta-analysis done on 25 randomized controlled trials in 2022 indicated that Ivermectin doesn't decrease the risk of mortality risk and the risk of mechanical ventilation requirements [ 59 ].…”
Section: Therapeutic Agentsmentioning
confidence: 99%